2012
DOI: 10.1160/th12-06-0426
|View full text |Cite
|
Sign up to set email alerts
|

Lipid levels do not influence the risk of venous thromboembolism

Abstract: SummaryStudies on the association between lipid profile and venous thromboembolism (VTE) are inconsistent. This could be caused by classical lipoproteins being inferior to apolipoproteins as markers for VTE risk. Therefore, we examined whether apolipoproteins are more strongly related to VTE than lipoproteins. For this analysis we used the PREVEND prospective community based observational cohort study. Levels of apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), total cholesterol (TC), high-density lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
3
16
0
1
Order By: Relevance
“…However, the majority of the reports on lipids and venous thrombosis in this meta-analysis were small case–control studies, and controlling for several confounders had not been possible [ 6 ]. Our results follow the majority of the longitudinal studies published after the aforementioned meta-analysis [ 6 ], that collectively showed little to no evidence of an association between the major lipid levels and risk of venous thrombosis [ 7 , 10 12 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the majority of the reports on lipids and venous thrombosis in this meta-analysis were small case–control studies, and controlling for several confounders had not been possible [ 6 ]. Our results follow the majority of the longitudinal studies published after the aforementioned meta-analysis [ 6 ], that collectively showed little to no evidence of an association between the major lipid levels and risk of venous thrombosis [ 7 , 10 12 ].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to the major lipids, fewer reports have addressed the relationship between venous thrombosis and levels of apo B and apo A1. In two cohort studies [ 8 , 12 ] neither apolipoprotein was associated with risk of venous thrombosis. In the other reports, an association between these apolipoproteins and venous thrombosis was restricted to certain subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association of hypertriglyceridemia with coronary artery disease is well known, [29] its association with venous thromboembolism is unclear and might be related to changes in the fibrinolytic system[30]. A few case reports describe thrombosis in ALL patients with hypertriglyceridemia [7, 12] but in our study, approximately 20% of patients with severe hypertriglyceridemia developed venous thromboembolism.…”
Section: Discussionmentioning
confidence: 59%
“…The hypothesis maintains that elevated levels of total cholesterol may be a risk factor for venous thromboembolism (VTE). Studies on the association between lipid profile and VTE are inconsistent, with some reporting that total cholesterol is the risk factor [24], while others report that lipid levels do not influence the risk of VTE; however, the levels of LDL are significantly associated with unprovoked VTE as revealed by univariate analysis [25]. Further, statins can prevent VTE [26].…”
Section: Discussionmentioning
confidence: 99%